2021
DOI: 10.25301/jpda.303.199
|View full text |Cite
|
Sign up to set email alerts
|

Modifications in Orthodontic Practice Post COVID Lockdown in Pakistan

Abstract: OBJECTIVE: To assess the frequency of positive changes in orthodontic practice in Pakistani governmental and private workplaces after lifting of COVID-19 lockdown. METHODOLOGY: This cross sectional questionnaire-based study was carried out on 143 Pakistani orthodontic practitioners for the duration of 3 months. A well-constructed, computerized closed ended questionnaire was designed at an online website i.e., google drive and the link was circulated through social media and e-mail. Change in dental practice wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…They concluded that fractures and abrasions were the commonest injuries received in such accidents. They also inferred that young males were more prone to have such accidents [12]. Ahmed et al conducted a study to focus on the risk factors of these injuries.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that fractures and abrasions were the commonest injuries received in such accidents. They also inferred that young males were more prone to have such accidents [12]. Ahmed et al conducted a study to focus on the risk factors of these injuries.…”
Section: Discussionmentioning
confidence: 99%